Description of a new diatom genus Dorofeyukea gen. nov. with remarks on phylogeny of the family Stauroneidaceae. Issue 1 (26th November 2018) - Kulikovskiy, Maxim; Maltsev, Yevhen; Andreeva, Svetlana; Glushchenko, Anton; Gusev, Evgeniy; Podunay, Yulia; Ludwig, Thelma Veiga; Tusset, Eduardo; Kociolek, John Patrick
Abstract : Type material of Navicula kotschyi was studied, and this species was transferred to Dorofeyukea gen. nov. as D. kotschyi comb. nov. Dorofeyukea was described on the basis of DNA sequence and morphological data. Additional species assigned to this genus that were previously included in Navicula include: D. ancisa comb. nov., D. grimmei comb. nov., D. ivatoensis comb. nov., D. orangiana comb. nov., D. rostellata comb. nov. & stat. nov., D. savannahiana comb. nov., D. tenuipunctata comb. nov., and D. texana comb. nov. All Dorofeyukea species share the same morphological features, including having a narrow stauroid fascia surrounded by 1–3 irregularly shortened striae, uniseriate, and weakly radiate striae, circular, or rectangular puncta in the striae that are covered internally by dome‐shaped hymenes, presence of a pseudoseptum at each apex and absence of septa. Partial DNA sequences of SSU and rbc L loci show Dorofeuykae belongs to the clade of stauroneioid diatoms together with Stauroneis, Prestauroneis, Craticula, Karayevia, Madinithidium, Fistulifera, Parlibellus, and, possibly, Schizostauron . A new species from the monoraphid genus Madinithidium, M. vietnamica sp. nov., was described based on valve and chloroplast morphology as well as DNA sequence data.